RESULTS OF EMPIRICAL RESEARCH OF BORDER GUARD INSPECTOR’S COMPETENCE IN PROFESSIONAL COMMUNICATION - Presniakova, Liudmyla (PSYCHOLOGICAL JOURNAL, 2017)
The results of empirical research of border guard inspector’s competence in professional communication have been presented in the article. The concept of «competence in professional communication» has been determined; its structure has been defined. Cognitive, personal and behavioral components of communicative, perceptual and interactive competence components of border guard inspectors in professional communication have been diagnosed. Diagnosis of cognitive component showed that border inspectors are good at general characteristics of professional communication, but they do not have deep knowledge in psychological features of the perceptual component of professional communication. It has been proved that the personal component of communicative competence of border guard inspectors is characterized by a high level of negative communication systems formation, low general communicative tolerance and high level of aggression and hostility in communication; their perceptual competence has undeveloped empathy ability formation; low level of reflexivity, focus on acceptance, understanding the partner and reaching a compromise in the interaction. The interactive competence is characterized by underdevelopment of border guard inspector’s leadership skills, dominance of conformation and avoidance styles in conflict situations, focus on professional communication on themselves. Diagnosis of the behavioural component showed that border guard inspectors have better developed communication skills, but perceptual skills are worse. It has been concluded that all competence components of border guard inspectors in professional communication are formed at the level lower than a middle one and they need further development.